Beginning AngularJS - Grant, Andrew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Beginning AngularJS is your step-by-step guide to learning the powerful AngularJS JavaScript framework. AngularJS is one of the most respected and innovative frameworks for building properly structured, easy-to-develop web applications. This book will teach you the absolute essentials, from downloading and installing AngularJS, to using modules, controllers, expressions, filters, and directives. Unlike many other books, you don't need experience with AngularJS or deep JavaScript knowledge to get started here. This book will begin by teaching you the JavaScript you need to know, and then you'll get into the basics of AngularJS. You'll learn powerful AngularJS techniques through clear instructions. With what you learn you'll be able to properly structure your code into manageable modules, understand the MVC design patterns, create expressive and adaptive HTML forms, communicate with servers and use other AngularJS services, use the powerful built-in directives, and learn how to create your own. This might all seem unknown now, but with this book you'll understand it all. AngularJS is a powerful framework, and one which may require you to think a little differently. This book will help you avoid the common pitfalls and get you up to speed, and building solid AngularJS applications, quickly and painlessly.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems